Avaliação da ação biodefensiva de ramnolipídios produzidos por Pseudomonas aeruginosa LBI 2A1 contra bactérias fitopatogênicas do feijão e da soja - Menezes, Aldry Ramos (Universidade Federal de São Carlos)
Brazil is internationally recognized as one of the largest producers of common bean (Phaseolus vulgaris) and soybean (Glycine max). This high productivity is made possible by the country’s favorable climatic conditions, such as high temperatures and abundant rainfall. The warm and humid climate makes Brazil one of the most productive agricultural regions in the world. Both legume species play a significant role in human nutrition due to their high nutritional value, being rich in proteins and carbohydrates and having a low caloric content, which makes them valuable for both human and animal diets. However, the productivity of these crops has been increasingly threatened by the emergence of bacterial diseases. The use of pesticides in seedlings contributes to the control of these pathogens, although, over time, it also promotes bacterial resistance. Microbial metabolites can serve as an alternative strategy for managing bacterial diseases in bean and soybean crops. Thus, this project aimed to evaluate the activity of biosurfactants produced by Pseudomonas aeruginosa LBI 2A1, known as rhamnolipids, in the control of bacterial diseases such as common bacterial blight (CBC) (Xanthomonas citri pv. fuscans) and bacterial pustule (Xanthomonas axonopodis pv. glycines). The methodology involved experiments in which different concentrations of the biosurfactant were added to the culture medium used for bacterial growth. After data collection, the results were analyzed using appropriate statistical methods. The antimicrobial effect of rhamnolipids proved to be effective against X. citri pv. fuscans, showing a significant reduction in microbial growth across the tested biosurfactant concentrations. In contrast, X. axonopodis pv. glycines demonstrated resistance to the biosurfactant, exhibiting an increase in bacterial population growth at the different rhamnolipid concentrations, indicating a positive effect on bacterial proliferation
Evaluation of the biodefensive action of rhamnolipids produced by Pseudomonas aeruginosa LBI 2A1 against phytopathogenic bacteria of common bean and soybean
Keywords: Biossurfactante; Crestamento-bacteriano-comum; Pústula-bacteriana; Ramnolipídios; Biosurfactant; Common bacterial blight; Bacterial pustule; Rhamnolipids; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO; 2. Fome Zero e Agricultura Sustentável